EFISIENSI PEMASARAN NANAS DENGAN BERBAGAI GRADE NANAS DI KABUPATEN LAMPUNG TENGAH - Zulkarnain Zulkarnain; Supriyadi Supriyadi; Supartini Supartini; Wintari Mandala; Amanda Putra Seta (Universitas Islam Bandung, 2020)
ABSTRACT The purpose of this study is to identify pineapple marketing channels and analyze the efficiency of pineapple marketing in Punggur District, Central Lampung. The research population was 175 pineapple farmers. The sampling technique was obtained based on the calculation of the slovin formula, then the proportion for the sample was obtained by sampling 54 pineapple farmers. Sampling was done in simple random sampling (simple random sampling). Besides, there are 6 collector traders, 2 large traders, and 4 retail traders. The data analysis used were marketing channels, marketing margin analysis, farmers’ share, and R/C ratio. Research location was in Punggur District, Central Lampung. The research period was conducted in May 2020. The results of the research are (1) there are two pineapple marketing channels in Punggur Subdistrict, Central Lampung, (2) pineapple marketing efficiency which is said to be more efficient is channel II and from the three pineapple grades, grade A produces greater profits than other grades. Keywords: farmer’s share, efficiency, margin, marketing ABSTRAKTujuan penelitian ini adalah mengidentifikasi saluran pemasaran nanas dan menganalisis efisiensi pemasaran nanas di Kecamatan Punggur Kabupaten Lampung Tengah. Populasi penelitian sebanyak 175 petani nanas. Teknik pengambilan sampel didapatkan berdasarkan perhitungan rumus slovin, kemudian dilakukan proporsi untuk sampel didapatkan sampel sebesar 54 petani nanas. Pengambilan sampel dilakukan secara acak sederhana (simple random sampling). Selain itu, terdapat 6 pedagang pengepul, 2 pedagang besar, dan 4 pedagang pengecer. Analisis data yang digunakan adalah saluran pemasaran, analisis marjin pemasaran, farmers’share, dan R/C ratio. Lokasi penelitian di Kecamatan Punggur Kabupaten Lampung Tengah. Waktu penelitian dilaksanakan pada bulan mei 2020. Hasil penelitian yaitu (1) terdapat dua saluran pemasaran nanas di Kecamatan Punggur Kabupaten Lampung Tengah, (2) efisiensi pemasaran nanas yang dikatakan lebih efisien adalah saluran II dan dari ketiga grade nanas, grade A menghasilkan keuntungan lebih besar dari grade lainnya. Kata kunci : efisiensi, farmer’s share, marjin, nanas